2017
DOI: 10.1038/s41598-017-13973-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in light sensitivity impact on brightness perception, vigilant attention and sleep in humans

Abstract: Artificial light endows a “round-the-clock”, 24-h/7-d society. Chronic exposure to light at night contributes to health hazards for humans, including disorders of sleep. Yet the influence of inter-individual traits, such as sex-differences, on light sensitivity remains to be established. Here we investigated potential sex-differences to evening light exposure of 40 lx at 6500 K (blue-enriched) or at 2500 K (non-blue-enriched), and their impact on brightness perception, vigilant attention and sleep physiology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 39 publications
0
63
0
1
Order By: Relevance
“…In addition to light conditions, other factors might also change the thresholds of sensitivity, such as gender, age, circadian phase, medical conditions, and light history. 5,11,39,43,44 Our findings have physiological and practical implications. Given that melatonin appears to be exquisitely sensitive to low light levels, melatonin suppression could be engaged as soon as one is exposed to light, even at relatively low intensities.…”
Section: T a B L E 1 Photoreceptor-weighted Illuminancesmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition to light conditions, other factors might also change the thresholds of sensitivity, such as gender, age, circadian phase, medical conditions, and light history. 5,11,39,43,44 Our findings have physiological and practical implications. Given that melatonin appears to be exquisitely sensitive to low light levels, melatonin suppression could be engaged as soon as one is exposed to light, even at relatively low intensities.…”
Section: T a B L E 1 Photoreceptor-weighted Illuminancesmentioning
confidence: 64%
“…Thus, we propose to use cautious interpretation before extrapolating our results to polychromatic lights and light‐emitting devices, and also to other settings such as real‐life conditions. In addition to light conditions, other factors might also change the thresholds of sensitivity, such as gender, age, circadian phase, medical conditions, and light history …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that perceptions of the environment and related psychological impacts differ across females and males. This has been found in studies of thermal comfort [76][77][78], visual perception [79,80], and cognitive performance [81,82]. Order effect has also been a potential moderating factor in similar experimental designs [27,61].…”
Section: Potential Moderator Variablesmentioning
confidence: 78%
“…; Chellappa et al . ). Sex differences in light sensitivity might play a key role for individual shift work interventions.…”
mentioning
confidence: 97%
“…As the authors point out, there is an 'apparent sex difference' as none of the six males included in the analysis advanced their circadian phase. Recently, two studies examining light sensitivity, circadian regulation and cognitive performance have shown sex differences (Santhi et al 2016;Chellappa et al 2017). Sex differences in light sensitivity might play a key role for individual shift work interventions.…”
mentioning
confidence: 99%